2005
DOI: 10.1007/s00167-005-0012-7
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic and muscle activity characteristics of multidirectional shoulder joint instability during elevation

Abstract: Alterations of shoulder motion have been suggested to be associated with shoulder disorders. The objective of this study was to perform a 3D motion analysis (kinematic and electromyographical) of skeletal elements and muscles of shoulder joint in patients with multidirectional instability. Fifteen patients with multidirectional instability and 15 normal controls were investigated during continuous elevation in the scapular plane. The spatial coordinates of 16 anatomical points of the shoulder to determine kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 26 publications
2
62
0
1
Order By: Relevance
“…There is evidence suggesting that scapular positioning is abnormal in patients with shoulder impingement syndrome, 2 symptoms of impingement, 10,11 atraumatic shoulder instability, 12 multidirectional shoulder joint instability, 13 and shoulder pain after neck dissection in cancer patients. 14,15 As no longitudinal study has yet been reported, it is not known if abnormal scapular positioning is a cause or consequence of shoulder pain or a secondary phenomenon caused by shoulder pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence suggesting that scapular positioning is abnormal in patients with shoulder impingement syndrome, 2 symptoms of impingement, 10,11 atraumatic shoulder instability, 12 multidirectional shoulder joint instability, 13 and shoulder pain after neck dissection in cancer patients. 14,15 As no longitudinal study has yet been reported, it is not known if abnormal scapular positioning is a cause or consequence of shoulder pain or a secondary phenomenon caused by shoulder pain.…”
Section: Discussionmentioning
confidence: 99%
“…Inappropriate control of scapular positioning has frequently been linked to shoulder and neck disorders. [6][7][8][9] Moreover, scientific evidence supporting abnormal scapular positioning in patients with shoulder impingement syndrome, 2 symptoms of shoulder impingement, 10,11 atraumatic shoulder instability, 12 multidirectional shoulder joint instability, 13 and shoulder pain after neck dissection in patients with cancer 14,15 is accumulating. One study has shown that physiotherapy (primarily exercise therapy targeting the scapulothoracic muscles) was superior over no treatment in patients with subacromial impingement syndrome.…”
mentioning
confidence: 98%
“…We have previously described the detailed ultrasound-based shoulder kinematic and electromyographic measurement method. 8,9 Assessment parameters…”
Section: Methods Of Biomechanic Measurementmentioning
confidence: 99%
“…8,9 With altered scapular kinematics being linked to a multitude of shoulder problems, the identification of changes in kinematics may allow for earlier detection of pathology and targeting of appropriate interventions. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] However, evaluation throughout the movement to maintain the distance between the acromion and humerus. 2.…”
Section: Dynamic Three-dimensional Ultrasound To Evaluate Scapular Momentioning
confidence: 99%